Microwave absorbing material as well as preparation method and application thereof
By using conductive fiber, metal oxide nanoparticles and chip layer conductive materials in the microwave absorbing material to build a conductive network, the lack of existing materials in the performance and application performance of the existing materials and the improvement of broadband absorption and mechanical performance improvement are achieved. Essence
Patent Information
- Application Number
- CN202411412529.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-10
Smart Images

Figure CN119371771A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of microwave materials, and in particular, relates to a microwave absorbing material and a preparation method and application thereof. Background Art
[0002] With the rapid development of 5G and 6G communication technologies, human lifestyles and production patterns have undergone revolutionary changes, becoming richer and more convenient than ever before. However, the infrastructure of these technologies, electronic devices, while bringing convenience to life, also continuously emit electromagnetic waves into the surrounding environment, causing electromagnetic pollution. This invisible pollution not only poses a potential threat to biological health, but may also interfere with the normal operation of nearby electronic devices.
[0003] To meet this challenge, researchers have proposed a variety of solutions, among which microwave absorbing materials have attracted much attention due to their excellent performance. However, there are relatively few microwave absorbing materials on the market, and they generally have poor microwave absorption performance, making it difficult to achieve effective breakthroughs in the comprehensive goals of "thin, light, wide, and strong" for microwave absorbing materials. In addition, there are still challenges in achieving broadband absorption at low filling ratios for existing microwave absorbing materials, which limits their application performance. Summary of the invention
[0004] The purpose of the present application is to provide a microwave absorbing material and a preparation method and application thereof, aiming to solve the problem that the existing microwave absorbing materials have poor microwave absorption performance and poor application performance to a certain extent.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] In a first aspect, the present application provides a microwave absorbing material, comprising the following raw material components in parts by weight:
[0007] Conductive fiber 1-5 parts,
[0008] 3 to 8 parts of metal oxide nanoparticles,
[0009] 0.3-0.8 parts of sheet conductive material,
[0010] Resin 90-95 parts;
[0011] In the microwave absorbing material, the zero-dimensional metal oxide nanoparticles, the one-dimensional conductive fibers and the two-dimensional sheet conductive material construct a spatially continuous conductive network.
[0012] In some possible implementations, the conductive fiber has a diameter of 5 μm to 15 μm and a length of 300 μm to 600 μm.
[0013] In some possible implementations, the average particle size of the metal oxide is 100 nm to 600 nm.
[0014] In some possible implementations, the sheet diameter of the sheet conductive material is 1 μm to 2 μm, and the thickness is 20 nm to 100 nm.
[0015] In some possible implementations, in the microwave absorbing material, the conductive fibers are distributed in an oriented manner, and the metal oxide nanoparticles and the sheet conductive material are distributed randomly.
[0016] In some possible implementations, the conductive fibers include chopped carbon fibers.
[0017] In some possible implementations, the metal oxide includes at least one of cerium oxide, nickel oxide, cobalt oxide, and iron oxide.
[0018] In some possible implementations, the sheet conductive material includes at least one of graphene, boron nitride, molybdenum disulfide, and black phosphorus.
[0019] In some possible implementations, the resin includes at least one of acrylonitrile-butadiene-styrene, polylactic acid, polyetheretherketone, polycarbonate, polyamide, and polyurethane.
[0020] In some possible implementations, the metal oxide includes hydrothermally synthesized cerium oxide.
[0021] In some possible implementations, the conductive fibers include glue-free virgin chopped carbon fibers.
[0022] In some possible implementations, the sheet conductive material includes graphene oxide.
[0023] In some possible implementations, the resin includes acrylonitrile-butadiene-styrene.
[0024] In some possible implementations, the microwave absorbing material is in a form of at least one of wires, particles, and powder.
[0025] In a second aspect, the present application provides a method for preparing a microwave absorbing material, comprising the following steps:
[0026] Obtaining raw material components including 1 to 5 parts of conductive fibers, 3 to 8 parts of metal oxide nanoparticles, 0.3 to 0.8 parts of sheet conductive materials and 90 to 95 parts of resin;
[0027] After the raw material components are dried, melt mixing is performed to make the zero-dimensional metal oxide nanoparticles, the one-dimensional conductive fibers and the two-dimensional sheet conductive material construct a spatially continuous conductive network, which is then extruded to obtain a microwave absorbing material.
[0028] In some possible implementations, the stirring speed of the molten mixture is 10 r / min to 20 r / min, the stirring time is 30 min to 90 min, and the temperature is 190° C. to 220° C.
[0029] In some possible implementations, the microwave absorbing material is in the form of wires with a diameter of 1 mm to 3 mm; or particles; or powder.
[0030] In some possible implementations, the metal oxide includes hydrothermally synthesized cerium oxide with an average particle size of 100 nm to 600 nm.
[0031] In some possible implementations, the conductive fibers include non-colloid chopped carbon fibers with a diameter of 5 μm to 15 μm and a length of 300 μm to 600 μm.
[0032] In some possible implementations, the sheet conductive material includes graphene oxide with a sheet diameter of 1 μm to 2 μm and a thickness of 20 nm to 100 nm.
[0033] In some possible implementations, the resin includes acrylonitrile-butadiene-styrene.
[0034] In some possible implementations, the preparation of the hydrothermally synthesized cerium oxide includes the steps of: dissolving a cerium salt in water, adding an alkaline substance to adjust the pH value to 10-12, reacting in a high-pressure reactor at a temperature of 150°C to 180°C for 10 to 24 hours, washing the reaction product after cooling, and separating and drying to obtain the hydrothermally synthesized cerium oxide.
[0035] In a third aspect, the present application provides a microwave absorbing product, which is made by 3D printing using the above-mentioned microwave absorbing material and / or the above-mentioned microwave absorbing material.
[0036] The microwave absorbing material provided in the first aspect of the present application comprises 1 to 5 parts of conductive fibers, 3 to 8 parts of metal oxide nanoparticles, 0.3 to 0.8 parts of sheet conductive materials and 90 to 95 parts of resin; wherein, if the content of conductive carbon fibers is too high, the brittleness of the microwave absorbing material will increase and the processing performance will deteriorate. If the content of metal oxide is too high, the density of the microwave absorbing material will increase, affecting the overall lightweight performance, and will also cause the uniformity of the material to decrease. If the content of graphene oxide is too high, the viscosity of the material will increase, making it difficult to process, and accumulation will form in the material, thereby affecting the uniformity of the electromagnetic wave absorption performance. Conductive fibers, metal oxide nanoparticles, and sheet conductive materials all have good conductivity and electromagnetic wave absorption characteristics. They absorb and attenuate the transmitted electromagnetic waves at the same time through different mechanisms such as dielectric loss, magnetic loss, and conductive loss. In addition, through the specific combination and interaction of three conductive fillers of zero-dimensional metal oxide nanoparticles, one-dimensional conductive fibers, and two-dimensional sheet conductive materials, a spatially continuous conductive and enhanced network is constructed in the microwave absorbing material to enhance its electromagnetic wave absorption capacity. Under the synergistic effect of these materials and combinations, microwave absorbing materials are endowed with efficient electromagnetic wave absorption capabilities. Microwave absorbing materials can effectively convert electromagnetic wave energy into heat energy or other forms of energy. Especially under the condition of low filling ratio, it can still achieve high-efficiency absorption in a wide band, which is expected to promote the development and application of microwave absorbing materials. In addition, two-dimensional sheet conductive materials can significantly improve the interlayer bonding strength of microwave absorbing material printed products, thereby improving the mechanical properties of printed parts, which can promote the development of microwave absorbing material technology and broaden its application potential in various fields. The microwave absorbing materials of this application help reduce electromagnetic pollution, and have a positive effect on protecting biological health and reducing interference with neighboring electronic devices. The development of absorbing material technology will promote technological progress and industrial upgrading in related industries, and drive economic growth in related fields such as new materials and 3D printing.
[0037] The second aspect of the present application provides a method for preparing a microwave absorbing material, which comprises obtaining raw material components such as 1 to 5 parts of conductive fibers, 3 to 8 parts of metal oxide nanoparticles, 0.3 to 0.8 parts of lamellar conductive materials, and 90 to 95 parts of resins, drying the raw material components, melt-mixing the materials, mixing the components thoroughly and evenly, and extruding the materials to obtain the microwave absorbing material. The preparation process is simple and suitable for large-scale industrial production and application. Among them, zero-dimensional metal oxide nanoparticles, one-dimensional conductive fibers, and two-dimensional lamellar conductive materials construct a spatially continuous conductive network, and the microwave absorbing material is endowed with efficient electromagnetic wave absorption capabilities through the specific combination and interaction of the three conductive fillers. Microwave absorbing materials can effectively convert electromagnetic wave energy into heat energy or other forms of energy, especially under conditions of low filling ratios, and can still achieve high-efficiency absorption over a wide frequency band, which is expected to promote the development and application of microwave absorbing materials.
[0038] The microwave absorbing product provided in the third aspect of the present application is made by 3D printing using the above-mentioned microwave absorbing material. The microwave absorbing material has a specific combination and interaction of three types of conductive fillers, and a spatially continuous conductive and enhanced network is constructed in the microwave absorbing material, which has excellent electromagnetic wave absorption capacity. It helps microwave absorbing products reduce electromagnetic pollution, and has a positive effect on protecting biological health and reducing interference with neighboring electronic devices. In addition, the two-dimensional sheet conductive material can significantly improve the interlayer bonding strength of microwave absorbing material printed products, improve the mechanical properties of printed microwave absorbing products, and broaden its application potential in various fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0040] Figure 1 It is a schematic flow chart of a method for preparing a microwave absorbing material provided in an embodiment of the present application;
[0041] Figure 2 1 is a schematic flow chart of a method for preparing a microwave absorbing wire provided in Example 1 of the present application;
[0042] Figure 3 1 is a SEM image of the ABS@CeO2 / rGO / CF composite microwave absorbing wire provided in Example 1 of the present application, wherein (a), (b) and (c) are SEM images of different observation positions;
[0043] Figure 4 The composite wire TGA thermogravimetric analysis test results (a) provided in Example 1, Comparative Example 1 and Comparative Example 2 of the present application; the MFR melt flowability test results (b);
[0044] Figure 5 It is a test diagram of the electromagnetic parameters of the wire provided by Examples 1 to 3 of the present application and Comparative Examples 1 to 2; wherein, (a) the real part of the complex dielectric constant, (b) the imaginary part of the complex dielectric constant, (c) the loss tangent of the complex dielectric constant, (d) the real part of the complex magnetic permeability, (e) the imaginary part of the complex magnetic permeability, (f) the loss tangent of the complex magnetic permeability;
[0045] Figure 61 is the reflection loss curve of the wire provided in Examples 1 to 3 and Comparative Examples 1 to 2 of the present application under different thickness conditions, wherein (a) MAT1 reflection loss curve, (b) MAT2 reflection loss curve, (c) MAT3 reflection loss curve, (d) MAT4 reflection loss curve, (e) MAT5 reflection loss curve, (f) is the reflection loss and impedance matching curve of MAT4 at a thickness of 2.2 mm;
[0046] Figure 7 These are interlayer bonding strength test graphs of interlayer bonding strength test pieces obtained by 3D printing of the wires provided in Examples 1 to 3 and Comparative Examples 1 to 2 of the present application, wherein (a) are pictures of printed products of ABS@CeO2 / rGO / CF composite materials with different ratios, and (b) are interlayer bonding strength comparison test graphs. DETAILED DESCRIPTION
[0047] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0048] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0049] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0050] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0051] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0052] The weight of the relevant components mentioned in the embodiments of the present specification can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present specification is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present specification. Specifically, the mass described in the embodiments of the present specification can be μg, mg, g, kg and other mass units known in the chemical industry.
[0053] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0054] In a first aspect, an embodiment of the present application provides a microwave absorbing material, comprising the following raw material components in parts by weight:
[0055] Conductive fiber 1-5 parts,
[0056] 3 to 8 parts of metal oxide nanoparticles,
[0057] 0.3-0.8 parts of sheet conductive material,
[0058] Resin 90-95 parts;
[0059] In microwave absorbing materials, zero-dimensional metal oxide nanoparticles, one-dimensional conductive fibers and two-dimensional lamellar conductive materials construct a spatially continuous conductive network.
[0060] The microwave absorbing material provided in the first aspect of the embodiment of the present application comprises 1 to 5 parts of conductive fibers, 3 to 8 parts of metal oxide nanoparticles, 0.3 to 0.8 parts of sheet conductive materials and 90 to 95 parts of resin; wherein, if the content of conductive carbon fibers is too high, the brittleness of the microwave absorbing material will increase and the processing performance will deteriorate. If the content of metal oxide is too high, the density of the microwave absorbing material will increase, affecting the overall lightweight performance, and will also cause the uniformity of the material to decrease. If the content of graphene oxide is too high, the viscosity of the material will increase, making it difficult to process, and accumulation will form in the material, thereby affecting the uniformity of the electromagnetic wave absorption performance. Conductive fibers, metal oxide nanoparticles, and sheet conductive materials all have good conductivity and electromagnetic wave absorption characteristics. They absorb and attenuate the transmitted electromagnetic waves at the same time through different mechanisms such as dielectric loss, magnetic loss, and conductive loss. In addition, through the specific combination and interaction of three conductive fillers of zero-dimensional metal oxide nanoparticles, one-dimensional conductive fibers, and two-dimensional sheet conductive materials, a spatially continuous conductive and enhanced network is constructed in the microwave absorbing material to enhance its electromagnetic wave absorption capacity. Under the synergistic effect of these materials and combinations, microwave absorbing materials are endowed with efficient electromagnetic wave absorption capabilities. Microwave absorbing materials can effectively convert electromagnetic wave energy into heat energy or other forms of energy. Especially under the condition of low filling ratio, it can still achieve high-efficiency absorption in a wide band, which is expected to promote the development and application of microwave absorbing materials. In addition, two-dimensional sheet conductive materials can significantly improve the interlayer bonding strength of microwave absorbing material printed products, thereby improving the mechanical properties of printed parts, which can promote the development of microwave absorbing material technology and broaden its application potential in various fields. The microwave absorbing material in the embodiment of the present application helps to reduce electromagnetic pollution, and has a positive effect on protecting biological health and reducing interference with neighboring electronic devices. The development of absorbing material technology will promote technological progress and industrial upgrading in related industries, and drive economic growth in related fields such as new materials and 3D printing.
[0061] In some implementations, in the microwave absorbing material, the conductive fibers are distributed in an oriented manner, and the metal oxide nanoparticles and the sheet conductive material are distributed irregularly. In this case, the three types of conductive fillers are combined in a specific form and interact with each other to construct a spatially continuous conductive and enhanced network in the microwave absorbing material, which can better improve the electromagnetic wave absorption capacity.
[0062] In some implementations, the diameter of the conductive fiber is 5 μm to 15 μm, and the length is 300 μm to 600 μm. In this case, the size of the conductive fiber not only ensures the conductivity of the one-dimensional linear conductive material, can absorb and attenuate the transmitted electromagnetic waves, but also ensures its dispersion uniformity and stability in the microwave absorbing material, ensures the processing performance and application performance of the microwave absorbing material, and avoids the problem of impedance mismatch caused by the conductive material being too large, and easy to cause clogging during the printing process. Exemplarily, the diameter of the conductive fiber can be 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, etc., typical but non-restrictive arbitrary point values or interval values between any two point values, and the length can be 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 600 μm, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0063] In some implementations, the conductive fiber includes chopped carbon fiber. In this case, the chopped carbon fiber is made by chopping carbon fiber filaments by a fiber cutting machine, and has the advantages of excellent electrical conductivity, uniform dispersion, diverse feeding methods, and simple process. It can improve the mechanical strength and wear resistance of the material, and its conductive property helps to improve the electromagnetic compatibility of the material.
[0064] In some implementations, the conductive fiber includes glue-free virgin chopped carbon fiber. In this case, glue-free virgin refers to a process in which the chopped carbon fiber is not treated with an adhesive or other binder during the production process. Glue-free virgin carbon fiber has better electrical conductivity and thermal conductivity, and can also improve the strength and heat resistance of the material and reduce the weight of the material. Since there is no additional adhesive layer, the carbon fiber can give full play to its inherent properties. The mechanical properties of the carbon fiber, such as strength and toughness, can be better retained, and the interface bonding between it and the resin matrix in the microwave absorbing material is purer, which is very beneficial for the manufacture of microwave absorbing materials.
[0065] In some implementations, the conductive fibers include non-colloid chopped carbon fibers with a diameter of 5 μm to 15 μm and a length of 300 μm to 600 μm, which can improve the mechanical strength and wear resistance of the material, while its conductive properties help improve the electromagnetic compatibility of the material.
[0066] In some implementations, the average particle size of the metal oxide is 100nm to 600nm. In this case, the metal oxide has a smaller particle size and a higher surface activity of the particles, which can effectively improve the electromagnetic wave absorption efficiency of the microwave absorbing material; at the same time, the particle size also ensures the dispersion stability of the metal oxide particles in the microwave absorbing material, avoids agglomeration between particles, and affects the absorption effect of the microwave absorbing material on electromagnetic waves. Exemplarily, the average particle size of the metal oxide can be 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0067] In some implementations, the metal oxide includes at least one of cerium oxide, nickel oxide, cobalt oxide, and iron oxide, all of which have good electromagnetic wave absorption capabilities and attenuation performance of transmitted electromagnetic waves. The hardness and wear resistance of the material can be improved, and its dielectric constant and dielectric loss can be adjusted within a certain frequency range, which helps to improve the performance of the absorbing composite material at a specific frequency.
[0068] In some implementations, the metal oxide includes hydrothermally synthesized cerium oxide. In this case, different synthesis methods, such as sol-gel method, coprecipitation method and hydrothermal method, have different effects on the particle size, crystal phase, morphology and surface chemical structure of cerium oxide, thereby affecting its optical, electrical and wave absorbing properties. The hydrothermal synthesis method can be carried out at a lower temperature, and can better control the morphology, particle size and crystal phase of nano cerium oxide, and can produce a more regular crystal structure. The cerium oxide particles obtained in this way usually have high dispersibility and uniformity, strong surface activity, and fewer lattice defects, thereby showing superior performance in wave absorbing applications, which helps to improve its wave absorbing ability.
[0069] In some implementations, the metal oxide includes hydrothermally synthesized cerium oxide with an average particle size of 100 nm to 600 nm, which can improve the hardness and wear resistance of the material, and at the same time, its dielectric constant and dielectric loss can be adjusted within a certain frequency range, which helps to improve the performance of the absorbing composite material at a specific frequency.
[0070] In some implementations, the sheet diameter of the sheet conductive material is 1 μm to 2 μm, and the thickness is 20 nm to 100 nm. In this case, the size of the two-dimensional sheet conductive material not only ensures that it has good electrical conductivity, but also facilitates the uniform distribution of the sheet conductive material in the microwave absorbing material, and constructs a spatially continuous conductive and enhanced network with zero-dimensional metal oxide nanoparticles and one-dimensional conductive fiber wires, thereby improving the mechanical properties and conductive loss properties of the microwave absorbing material. Exemplarily, the sheet diameter of the sheet conductive material can be 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, etc., typical but non-restrictive arbitrary point values or interval values between any two point values; the thickness can be 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 80 nm, 100 nm, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0071] In some implementations, the lamellar conductive material includes at least one of graphene (rGO), boron nitride (h-BN), molybdenum disulfide (MoS2), and black phosphorus; these lamellar conductive materials all have excellent layered structures and conductive properties, and can be used in different electromagnetic wave absorption and heat conduction applications. In addition, the use of two-dimensional lamellar conductive materials enhances the interlayer bonding strength of microwave absorbing material printed products, solves the problem of insufficient interlayer bonding strength in traditional fused deposition modeling printing technology, and thus significantly improves the overall mechanical properties of composite material prints. The high conductivity of lamellar conductive materials improves the electrical properties of the material, and the large specific surface area also helps to improve the interaction between the material and electromagnetic waves, thereby enhancing the absorption efficiency.
[0072] In some implementations, the sheet conductive material includes graphene oxide. In this case, compared to graphene, the surface of graphene oxide has abundant oxygen-containing functional groups, which help graphene to form stronger interfacial bonds with other components such as conductive fibers, resins and metal oxides. Therefore, graphene oxide exhibits better dispersibility and compatibility in microwave absorbing materials, especially better stability when compounded with resins, thereby improving the comprehensive performance of microwave absorbing materials. In addition, the use of two-dimensional graphene oxide enhances the interlayer bonding strength of microwave absorbing material printed products, solves the problem of insufficient interlayer bonding strength in traditional fused deposition modeling printing technology, and thus significantly improves the overall mechanical properties of composite material prints.
[0073] In some implementations, the sheet conductive material includes graphene oxide with a sheet diameter of 1 μm to 2 μm and a thickness of 20 nm to 100 nm. The high conductivity of rGO improves the electrical properties of the material, and the large specific surface area also helps to improve the interaction between the material and electromagnetic waves, thereby enhancing the absorption efficiency.
[0074] In some implementations, the resin includes at least one of acrylonitrile butadiene styrene (ABS), polylactic acid, polylactic acid, polyether ether ketone (PEEK), polycarbonate (PC), polyamide (PA), and polyurethane (PU). These resins all have excellent mechanical properties and chemical stability. As a matrix material, after being mixed with other components, it not only maintains its original advantages, but also obtains the ability to absorb electromagnetic waves due to the addition of fillers.
[0075] In some implementations, the resin includes acrylonitrile-butadiene-styrene, i.e., ABS resin. In this case, acrylonitrile-butadiene-styrene is composed of three monomers: acrylonitrile, butadiene, and styrene, and has the hardness and chemical resistance of acrylonitrile, the toughness and cold resistance of butadiene, and the rigidity and processability of styrene. This combination allows the ABS resin to have good toughness while maintaining high rigidity, and can effectively absorb microwave energy and resist the mechanical stress generated thereby. The molding shrinkage of the ABS resin is small, which helps to maintain the stability and precision of the product size during the manufacturing process of the microwave absorbing material. At the same time, the ABS resin has good heat resistance, excellent wear resistance and strain resistance, and can maintain stable performance under certain high temperature environments. At the same time, its dimensional stability is also good, and it is not easy to have significant dimensional changes due to temperature changes, which is particularly important for the long-term use of microwave absorbing materials. In addition, the ABS resin has good processing properties and can be processed by a variety of molding processes such as injection molding and extrusion, which makes the ABS resin have greater flexibility in the manufacturing process of microwave absorbing materials, and the production process and product structure can be adjusted according to specific needs.
[0076] In some implementations, the microwave absorbing material comprises at least one of a wire, a particle, and a powder. The microwave absorbing material of the present application may be in a variety of morphologies such as a wire, a particle, and a powder to meet different application requirements. For example, a particle or powder morphology is usually used in injection molding, compression molding or other material preparation technologies, while a wire is suitable for molding processes such as 3D printing.
[0077] The microwave absorbing material of the above-mentioned embodiment of the present application can be prepared by the following embodiment method.
[0078] In a second aspect, the present application provides a method for preparing a microwave absorbing material, as shown in the attached Figure 1 As shown, the following steps are included:
[0079] S10. Obtaining a raw material component comprising 1 to 5 parts of conductive fibers, 3 to 8 parts of metal oxide nanoparticles, 0.3 to 0.8 parts of a sheet conductive material and 90 to 95 parts of a resin;
[0080] S20. After drying the raw material components, melt mixing is performed to allow the zero-dimensional metal oxide nanoparticles, one-dimensional conductive fibers and two-dimensional sheet conductive materials to construct a spatially continuous conductive network, which is then extruded to obtain a microwave absorbing material.
[0081] The preparation method of the microwave absorbing material provided in the embodiment of the present application is to obtain raw material components such as 1 to 5 parts of conductive fibers, 3 to 8 parts of metal oxide nanoparticles, 0.3 to 0.8 parts of lamellar conductive materials and 90 to 95 parts of resin, dry the raw material components, melt mix them, make the components fully and evenly mixed, and extrude them to obtain the microwave absorbing material. The preparation process is simple and suitable for industrial large-scale production and application. Among them, zero-dimensional metal oxide nanoparticles, one-dimensional conductive fibers and two-dimensional lamellar conductive materials construct a spatially continuous conductive network, and the microwave absorbing material is endowed with efficient electromagnetic wave absorption ability through the specific combination form and interaction of the three conductive fillers. Microwave absorbing materials can effectively convert electromagnetic wave energy into heat energy or other forms of energy, especially under the condition of low filling ratio, and can still achieve high-efficiency absorption over a wide frequency band, which is expected to promote the development and application of microwave absorbing materials.
[0082] In the above step S10:
[0083] In some implementations, the conductive fiber includes non-colloid chopped carbon fibers with a diameter of 5 μm to 15 μm and a length of 300 μm to 600 μm. In this case, the conductive fiber has better electrical conductivity and thermal conductivity, and can also improve the strength and heat resistance of the material, and reduce the weight of the material, which is beneficial to the manufacture of microwave absorbing materials. The mechanical strength and wear resistance of the material can be improved, and its conductive properties help to improve the electromagnetic compatibility of the material.
[0084] In some implementations, the lamellar conductive material includes graphene oxide with a sheet diameter of 1 μm to 2 μm and a thickness of 20 nm to 100 nm. In this case, the lamellar conductive material has a better layered structure and conductive properties, and exhibits better dispersibility and compatibility in microwave absorbing materials. At the same time, it can better enhance the interlayer bonding strength of microwave absorbing material printed products, solve the problem of insufficient interlayer bonding strength in traditional fused deposition modeling printing technology, and thus significantly improve the overall mechanical properties of composite material prints. The high conductivity of rGO may also improve the electrical properties of the material, and the large specific surface area also helps to improve the interaction between the material and electromagnetic waves, thereby enhancing the absorption efficiency.
[0085] In some implementations, the resin includes acrylonitrile butadiene styrene. In this case, acrylonitrile butadiene styrene (ABS) resin as a base material of the microwave absorbing material has advantages in terms of physical properties, processing properties, and cost-effectiveness. ABS, as a base material, has good processing properties and mechanical properties. After being mixed with other components, it not only maintains its original advantages, but also obtains the ability to absorb electromagnetic waves due to the addition of fillers. ABS can be used as a commonly used 3D printing material.
[0086] In some implementations, the metal oxide includes hydrothermally synthesized cerium oxide with an average particle size of 100nm to 600nm. In this case, the metal oxide has strong surface activity and fewer lattice defects, and exhibits superior performance in wave absorbing applications, which helps to improve its wave absorbing ability. The hardness and wear resistance of the material can be improved, and its dielectric constant and dielectric loss can be adjusted within a certain frequency range, which helps to improve the performance of the wave absorbing composite material at a specific frequency.
[0087] In some implementations, the preparation of hydrothermally synthesized cerium oxide includes the steps of: dissolving a cerium salt in water, adding an alkaline substance to adjust the pH value to 10-12, reacting in a high-pressure reactor at a temperature of 150°C to 180°C for 10 to 24 hours, washing the reaction product after cooling, and separating and drying to obtain hydrothermally synthesized cerium oxide.
[0088] In some implementations, in addition to Ce(NO3)3·6H3O, other cerium-containing compounds can be selected as precursors, such as cerium nitrate (Ce(NO3)3), cerium acetate (Ce(CH3COO)3), cerium chloride (CeCl3), etc. These compounds can also form CeO2 nanoparticles during the hydrothermal synthesis process. It is only necessary to adjust the synthesis conditions to adapt to the solubility and reactivity of different precursors. Ce(NO3)3·6H3O is preferred.
[0089] In some implementations, the alkaline substance includes ammonia, sodium hydroxide (NaOH), potassium hydroxide (KOH) or urea (CO(NH2)2), etc. These alkaline substances can adjust the pH value of the solution and promote Ce 3+ Oxidized to CeO2 nanoparticles. The alkaline substance has different effects on the morphology, size and dispersibility of the final product, and ammonia water is preferred.
[0090] In some specific embodiments, first, 1mmol Ce(NO3)3·6H2O is dissolved in 60ml deionized water, and after manual stirring until completely dissolved, ammonia water is slowly added dropwise to adjust the pH value of the mixed solution to 11. Then, it is transferred to a high-pressure reactor with a polytetrafluoroethylene liner, and the reactor is placed in a vacuum heating furnace, the furnace temperature is set to 160 degrees Celsius, and the reaction is continued for 12 hours. After the reaction is completed, the power of the heating furnace is turned off, and the high-pressure reactor is allowed to cool naturally to room temperature in the furnace. Then, the solution in the high-pressure reactor is poured out, and it is washed with deionized water and anhydrous ethanol for multiple times to remove residual impurities. Finally, the cleaned product is dried at 80°C until completely dry to obtain a light yellow cerium oxide nanoparticle product.
[0091] In the above step S20:
[0092] In some implementations, the stirring speed of the molten mixture is 10 r / min to 20 r / min, the stirring time is 30 min to 90 min, and the temperature is 190° C. to 220° C. In this case, it can be fully ensured that the zero-dimensional metal oxide nanoparticles, the one-dimensional conductive fibers, and the two-dimensional sheet conductive materials are evenly dispersed in the resin, so that the conductive fibers are oriented and distributed, and the metal oxide nanoparticles and the sheet conductive materials are randomly distributed, so as to construct a spatially continuous conductive and reinforcing network in the resin matrix.
[0093] In some implementations, the microwave absorbing material is in the form of a wire with a diameter of 1 mm to 3 mm; or a particle; or a powder. In this case, the microwave absorbing material can be in the form of a wire, a particle, a powder, etc., which mainly depends on the specific application requirements. For example, the particle or powder form is usually used in injection molding, compression molding or other material preparation technologies. The wire is mainly suitable for 3D printing. The microwave absorbing material can be prepared into a morphology that meets the application requirements according to the molding process of the actual application.
[0094] In some embodiments, the diameter of the microwave absorbing material wire directly affects the fluidity and precision of the material during the printing process. Thicker wires (such as 2.85mm) usually require higher extrusion temperatures and larger nozzle diameters, which are suitable for larger-scale printing; while thinner wires (such as 1.75mm) are more commonly used in fine printing, which helps to improve printing accuracy, control details, and ensure uniform supply of materials. Among them, the wire diameter of 1.75mm is one of the common standard sizes in 3D printing. This diameter has good compatibility and can be used directly on standard 3D printing equipment. Especially printers used for FDM (fused deposition modeling) technology.
[0095] In a third aspect, an embodiment of the present application provides a microwave absorbing product, which is made by 3D printing using the above-mentioned microwave absorbing material and / or the above-mentioned microwave absorbing material.
[0096] The microwave absorbing product provided in the embodiment of the present application is made by 3D printing using the above-mentioned microwave absorbing material. The microwave absorbing material has a specific combination and interaction of three types of conductive fillers, and a spatially continuous conductive and enhanced network is constructed in the microwave absorbing material, which has excellent electromagnetic wave absorption capacity. It helps microwave absorbing products reduce electromagnetic pollution, and has a positive effect on protecting biological health and reducing interference with neighboring electronic devices. In addition, the two-dimensional sheet conductive material can significantly improve the interlayer bonding strength of the microwave absorbing material printed product, improve the mechanical properties of the printed microwave absorbing product, and broaden its application potential in various fields.
[0097] In some implementations, the fused deposition modeling (FDM) 3D printing technology, with its layer-by-layer printing method, can quickly produce absorbing layers or structures, with the advantages of low cost, high production efficiency and low technical requirements for operators, and has the potential for mass production of microwave absorbing products. By improving the application of FDM 3D printing technology in the manufacture of absorbing materials, low-cost and high-efficiency mass production can be achieved. The application of 3D printing technology, especially fused deposition modeling (FDM) technology, makes it possible to mass produce absorbing layers / structures.
[0098] In some implementations, the microwave absorbing products of the embodiments of the present application achieve a technological breakthrough in the field of electromagnetic wave absorbing materials through the combination of materials and processes, promote the development of microwave absorbing material technology, and broaden its application potential in various fields. Microwave absorbing products help reduce electromagnetic pollution and have a positive effect on protecting biological health and reducing interference with adjacent electronic devices.
[0099] In some implementations, due to the increasingly serious problem of electromagnetic pollution, the microwave absorbing products of the embodiments of the present application have broad market application prospects, especially in the fields of aerospace, medical treatment, construction, and automobile manufacturing.
[0100] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to significantly demonstrate the improved performance of the microwave absorbing materials and preparation methods and applications of the embodiments of the present application, the above technical solutions are illustrated by means of multiple embodiments below.
[0101] The information of some raw material components used in the following specific examples of this application is as follows:
[0102] a. Ce(NO3)3·6H2O, manufacturer: Aladdin Biotechnology Co., Ltd., granular, AR, ≥95%;
[0103] b. Ammonia water: NH3·H2O, manufacturer: Jiangsu Aikang Biopharmaceutical R&D Co., Ltd.;
[0104] c. Few-layer graphene oxide (rGO; Manufacturer: Shenzhen Suiheng Co., Ltd.;
[0105] d. Acrylonitrile-butadiene-styrene: C 45 H 51 N3X2; Manufacturer: Zhenjiang Chimei Chemical Co., Ltd. Average particle size 75μm;
[0106] e. Glue-free virgin cut carbon fiber: CF; Manufacturer: Toray Carbon Fiber Guangdong Co., Ltd. Normal length 350μm.
[0107] Example 1
[0108] An ABS@CeO2 / rGO / CF composite microwave absorbing wire material, including raw material components: 3 parts by mass of non-colloid chopped carbon fiber (CF, average diameter of about 10 μm, length of about 500 μm); 5 parts by mass of hydrothermally synthesized cerium oxide nanoparticles (CeO2, average particle size of 500 nm); 0.5 parts by mass of graphene oxide (rGO, sheet size of 1 to 2 μm, sheet thickness of about 50 nm); 91.5 parts by mass of acrylonitrile-butadiene-styrene ABS ternary resin particles. The schematic diagram of its preparation process is shown in the attached figure. Figure 2 shown.
[0109] The preparation of CeO2 nanoparticle material includes the following steps:
[0110] First, 1mmol Ce(NO3)3·6H2O was dissolved in 60ml deionized water, and after manual stirring until completely dissolved, ammonia water was slowly added dropwise to adjust the pH value of the mixed solution to 11. Then, it was transferred to a high-pressure reactor with a polytetrafluoroethylene liner, and the reactor was placed in a vacuum heating furnace, the furnace temperature was set to 160 degrees Celsius, and the reaction was continued for 12 hours. After the reaction was completed, the power of the heating furnace was turned off, and the high-pressure reactor was allowed to cool naturally to room temperature in the furnace. Next, the solution in the high-pressure reactor was poured out and washed with deionized water and anhydrous ethanol for multiple times to remove residual impurities. Finally, the washed product was dried at 80°C until completely dry to obtain a light yellow cerium oxide nanoparticle product.
[0111] The preparation of ABS@CeO2 / rGO / CF composite microwave absorbing wire includes the following steps:
[0112] First, take an appropriate amount of ABS pellets and put them into the oven for drying to remove moisture. Set the oven temperature to 60°C and the drying time to 12h. Then, weigh the formula amount of ABS, CeO2, CF, and rGO materials, pre-mix them in a container, and stir them manually for about 5min. After manual stirring, transfer them to a low-speed mechanical mixer for further mixing, set the mixer speed to 15r / min, and the stirring time to 50min. During the stirring process, turn on the power of the micro twin-screw extruder, set the temperatures of each area of the extruder to 190°C, 200°C, 220°C, and 200°C for preheating, and the preheating time is 1h. After the extruder is preheated, the extrusion speed is set to 10r / min, and the mixed material is put into the extruder hopper in batches. At the same time, the cooling device, laser diameter gauge and wire winding machine are turned on to cool, monitor and collect the extruded wire. The wire diameter is controlled at about 1.75mm by adjusting the speed of the wire winding machine to obtain ABS@CeO2 / rGO / CF composite microwave absorbing wire, which is marked as MAT4.
[0113] Example 2
[0114] An ABS@CeO2 / rGO / CF composite microwave absorbing wire, which differs from Example 1 in that the raw material components include: 3 parts by mass of non-colloid chopped carbon fibers (CF, average diameter of about 10 μm, length of about 500 μm); 5 parts by mass of hydrothermally synthesized cerium oxide nanoparticles (CeO2, average particle size of 500 nm); 0.3 parts by mass of graphene oxide (rGO, sheet size of 1 to 2 μm, sheet thickness of about 50 nm); 91.7 parts by mass of acrylonitrile-butadiene-styrene ABS ternary resin particles. The preparation steps and conditions are the same as those of Example 1, and the obtained ABS@CeO2 / rGO / CF composite microwave absorbing wire is marked as MAT3.
[0115] Example 3
[0116] An ABS@CeO2 / rGO / CF composite microwave absorbing wire, which differs from Example 1 in that the raw material components include: 3 parts by mass of non-colloid chopped carbon fibers (CF, average diameter of about 10 μm, length of about 500 μm); 5 parts by mass of hydrothermally synthesized cerium oxide nanoparticles (CeO2, average particle size of 500 nm); 0.8 parts by mass of graphene oxide (rGO, sheet size of 1 to 2 μm, sheet thickness of about 50 nm); 91.2 parts by mass of acrylonitrile-butadiene-styrene ABS ternary resin particles. The preparation steps and conditions are the same as those of Example 1, and the obtained ABS@CeO2 / rGO / CF composite microwave absorbing wire is marked as MAT5.
[0117] Comparative Example 1 [ABS]
[0118] Pure ABS resin is used as comparative example 1, and is marked as MAT1.
[0119] Comparative Example 2 [ABS+CF]
[0120] An ABS@CF composite microwave absorbing wire, marked as MAT2, is different from Example 1 in that the raw material components include: 3 parts by mass of non-colloid virgin chopped carbon fiber (CF, with an average diameter of about 10 μm and a length of about 500 μm); and 97 parts by mass of acrylonitrile-butadiene-styrene ABS ternary resin particles. The preparation steps and conditions are the same as those of Example 1.
[0121] In order to verify the progress of the embodiments of the present application, the following performance tests were performed on the above embodiments and comparative examples respectively:
[0122] 1. The cross section of the ABS@CeO2 / rGO / CF composite microwave absorbing wire (labeled as MAT4) prepared in Example 1 was observed by scanning electron microscopy. Figure 3 As shown in the figure, (a), (b) and (c) are SEM images of different observation sites. Figure 3 It can be seen that CF, cerium oxide and rGO are uniformly distributed in the resin matrix. CF shows obvious orientation, and its axis is roughly parallel to the axis of the wire. In contrast, CeO2 nanoparticles and rGO show irregular distribution inside the wire due to their smaller size. This uniform distribution design at the microscale helps to build a spatially continuous conductive and reinforcing network, thereby improving the mechanical properties and conductive loss properties of the composite material.
[0123] 2. The thermal stability and melt fluidity of 3D printing wires are key factors that determine their printability and the quality of printed products. In order to evaluate these properties, the composite wires provided in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to thermodynamic performance tests, respectively. The TGA thermogravimetric analysis test results are shown in the attached figure. Figure 4 As shown in (a); the MFR melt flow test results are shown in the attached Figure 4 Middle (b).
[0124] It can be seen that the TGA results show that the starting point of the thermal weight loss of all wires is more than 300°C, indicating that the composite wires and their internal fillers in the embodiments of the present application have good thermal stability. From the perspective of residual mass, the final residual mass ratio of the MAT1 material composed of pure ABS resin is 0.87%. After adding CF, the residual mass of the MAT2 material increases, and the residual mass of the MAT3 material with CeO2 and rGO is further increased to 7.21%. These results confirm the thermal stability of the composite materials in the embodiments of the present application and show that the distribution of the fillers is relatively uniform.
[0125] The MFR test results reveal the changes in the melt fluidity of the wire. The addition of CF reduces the flow properties of the resin, while the addition of CeO2 and rGO increases the melt flow rate of the material; this phenomenon is also reflected in the wire extrusion process, that is, at the same extrusion speed, the speed of the wire winding machine needs to be set higher to adapt to the changes in material fluidity.
[0126] 3. Dielectric constant and magnetic permeability are key parameters for evaluating the microwave absorption performance of materials, which together determine the material's ability to respond to electromagnetic waves. Based on this, for the wires provided in Examples 1 to 3 and Comparative Examples 1 to 2, the dimensions of the waveguide products provided in accordance with GB / T 35679-2017 are 72.14×34.04×3mm, 47.55×22.15×3mm, 34.85×15.80×3mm, 22.86×10.16×3mm and 15.80×7.90×3mm, respectively. The electromagnetic parameters of the 3D printed products of the five wires were tested using the waveguide method: the prepared wires were printed using a printer to print a coaxial waveguide test piece. The printer parameters were set to a nozzle temperature of 220°C, a hot bed temperature of 65°C, an extrusion speed of 100mm / s, a nozzle diameter of 0.6mm, a layer height of 0.2mm, and a filling rate of 100%. The electromagnetic parameters of the printed waveguide product were tested to obtain its electromagnetic parameters in the 2-18 GHz frequency band, and the electromagnetic parameters were imported into the CST Studio software to calculate the reflection loss of the composite film.
[0127] The test results are as attached Figure 5As shown, (a) the real part of the complex dielectric constant, (b) the imaginary part of the complex dielectric constant, (c) the loss tangent of the complex dielectric constant, (d) the real part of the complex magnetic permeability, (e) the imaginary part of the complex magnetic permeability, and (f) the loss tangent of the complex magnetic permeability. It can be seen that the imaginary part of the dielectric constant of the MAT1 product composed of pure resin is almost zero, indicating that the electromagnetic loss capacity of the material is limited. With the addition of short-cut CF, the real and imaginary parts of the dielectric constant of the MAT2 product increased significantly, indicating that the introduction of CF enhances the microwave absorption capacity of the material. Compared with the MAT2 product, the MAT3 product added two materials, CeO2 and rGO, and its real part of the dielectric constant was further improved, but the imaginary part of the dielectric constant in the 10-18GHz frequency band was indeed reduced. This phenomenon can be attributed to the fact that the addition of the magnetic material cerium oxide increases the magnetic loss capacity of the composite material, indicating that cerium oxide has a regulating effect on the impedance matching ability of the material system. In the MAT4 product, the content of rGO was further increased, the real part of the dielectric constant decreased, but the imaginary part was enhanced. However, in MAT5 products, further increase in rGO content leads to deterioration of microwave absorption performance. This may be due to the impedance mismatch caused by excessive rGO. The above results show that the introduction of CeO2 and the appropriate increase in rGO content are beneficial to improving the impedance matching performance and loss capacity of the composite material, which is crucial to improving the microwave absorption performance of the material.
[0128] 4. According to the transmission line theory, the reflection loss curves of different materials provided in Examples 1 to 3 and Comparative Examples 1 to 2 under different thickness conditions are obtained, as shown in the attached figure. Figure 6 As shown, (a) MAT1 reflection loss curve, (b) MAT2 reflection loss curve, (c) MAT3 reflection loss curve, (d) MAT4 reflection loss curve, (e) MAT5 reflection loss curve, the 1.5mm to 5.0mm size in the test figures (a) to (e) is the thickness used in the reflectivity calculation, and the reflectivity of the plate under different thickness conditions is calculated based on the electromagnetic parameters of the material obtained from the test; (f) is the reflection loss and impedance matching curve of MAT4 at a thickness of 2.2mm.
[0129] It can be seen that the attenuation capacity of pure resin to electromagnetic waves is very limited. With the addition of chopped carbon fibers, the electromagnetic loss capacity of the composite material is enhanced, indicating that the chopped carbon fibers give the ABS resin wave-absorbing properties. With the addition of rGO and cerium oxide nanoparticles, the absorption performance of the composite material system to electromagnetic waves is further improved. When the rGO mass fraction reaches 0.5wt%, that is, the MAT4 material achieves the widest effective absorption bandwidth (EAB = 6.68GHz) and the minimum reflection loss RLmin = -40.9dB (representing 99.99% of the electromagnetic waves are absorbed) under the condition of 2.2mm thickness. With the further increase of rGO content, the conductivity of the composite material also increases, which destroys the impedance matching performance of the material, resulting in the inability of electromagnetic waves to enter the material and be effectively attenuated.
[0130] 5. The interlayer bonding strength test pieces of the five materials provided in Examples 1 to 3 and Comparative Examples 1 to 2 were printed by FDM 3D printing technology: the printer parameters were set to a nozzle temperature of 220°C, a hot bed temperature of 65°C, an extrusion speed of 100 mm / s, a nozzle diameter of 0.6 mm, a layer height of 0.2 mm, and a filling rate of 100%. The interlayer bonding strength test pieces obtained by printing were tested to obtain the interlayer bonding strength of materials with different ratios. The test results are shown in the figure. Figure 7 As shown in the figure, (a) pictures of printed products of ABS@CeO2 / rGO / CF composite materials with different ratios, and (b) comparison test diagram of interlayer bonding strength. It can be seen that increasing the content of rGO can improve the interlayer bonding strength of the composite material, and the improvement of interlayer bonding strength helps to improve the overall load-bearing performance of the printed product.
[0131] The performance test data of the composite wires and printed products provided in Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Table 1 below:
[0132] Table 1
[0133]
[0134] Note: i represents the imaginary part.
[0135] From the above test results, it can be seen that the microwave absorbing material of the embodiment of the present application, which includes 1 to 5 parts of conductive fibers, 3 to 8 parts of metal oxide nanoparticles, 0.3 to 0.8 parts of sheet conductive materials, and 90 to 95 parts of resin as raw material components, has a higher melt flow rate, dielectric constant, magnetic permeability, etc., exhibits better microwave absorption performance, and the printed parts also exhibit a higher interlayer bonding strength.
[0136] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A microwave absorbing material, characterized in that: The invention comprises the following raw material components in parts by weight: Conductive fiber 1-5 parts, 3 to 8 parts of metal oxide nanoparticles, 0.3-0.8 parts of sheet conductive material, Resin 90-95 parts; In the microwave absorbing material, the zero-dimensional metal oxide nanoparticles, the one-dimensional conductive fibers and the two-dimensional sheet conductive material construct a spatially continuous conductive network.
2. The microwave absorbing material according to claim 1, characterized in that: The conductive fiber has a diameter of 5 μm to 15 μm and a length of 300 μm to 600 μm; And / or, the average particle size of the metal oxide is 100nm to 600nm; And / or, the sheet diameter of the sheet conductive material is 1 μm to 2 μm, and the thickness is 20 nm to 100 nm; And / or, in the microwave absorbing material, the conductive fibers are distributed in an oriented manner, and the metal oxide nanoparticles and the sheet conductive material are distributed randomly.
3. The microwave absorbing material according to claim 1 or 2, characterized in that: The conductive fibers include chopped carbon fibers; And / or, the metal oxide includes at least one of cerium oxide, nickel oxide, cobalt oxide, and iron oxide; And / or, the sheet conductive material includes at least one of graphene, boron nitride, molybdenum disulfide, and black phosphorus; And / or, the resin includes at least one of acrylonitrile-butadiene-styrene, polylactic acid, polyetheretherketone, polycarbonate, polyamide, and polyurethane.
4. The microwave absorbing material according to claim 3, characterized in that: The metal oxide includes hydrothermally synthesized cerium oxide; and / or, the conductive fibers include glue-free virgin chopped carbon fibers; And / or, the sheet conductive material includes graphene oxide; And / or, the resin includes acrylonitrile-butadiene-styrene.
5. The microwave absorbing material according to any one of claims 1 to 2 or 4, characterized in that: The microwave absorbing material may be in the form of at least one of wire, granule, and powder.
6. A method for preparing a microwave absorbing material, characterized in that: The following steps are involved: Obtaining raw material components including 1 to 5 parts of conductive fibers, 3 to 8 parts of metal oxide nanoparticles, 0.3 to 0.8 parts of sheet conductive materials and 90 to 95 parts of resin; After the raw material components are dried, melt mixing is performed to make the zero-dimensional metal oxide nanoparticles, the one-dimensional conductive fibers and the two-dimensional sheet conductive material construct a spatially continuous conductive network, which is then extruded to obtain a microwave absorbing material.
7. The method for preparing a microwave absorbing material according to claim 6, characterized in that: The stirring speed of the molten mixture is 10r / min to 20r / min, the stirring time is 30min to 90min, and the temperature is 190°C to 220°C; And / or, the microwave absorbing material is in the form of wires with a diameter of 1 mm to 3 mm; or particles; or powder.
8. The method for preparing a microwave absorbing material according to claim 6 or 7, characterized in that: The metal oxide includes hydrothermally synthesized cerium oxide with an average particle size of 100nm to 600nm; And / or, the conductive fibers include non-colloid chopped virgin carbon fibers having a diameter of 5 μm to 15 μm and a length of 300 μm to 600 μm; And / or, the sheet conductive material comprises graphene oxide with a sheet diameter of 1 μm to 2 μm and a thickness of 20 nm to 100 nm; And / or, the resin includes acrylonitrile-butadiene-styrene.
9. The method for preparing a microwave absorbing material according to claim 8, characterized in that: The preparation of the hydrothermally synthesized cerium oxide comprises the steps of: dissolving a cerium salt in water, adding an alkaline substance to adjust the pH value to 10-12, reacting in a high-pressure reactor at a temperature of 150° C. to 180° C. for 10-24 hours, washing the reaction product after cooling, and separating and drying to obtain the hydrothermally synthesized cerium oxide.
10. A microwave absorbing product, characterized in that: A microwave absorbing product is produced by 3D printing using the microwave absorbing material according to any one of claims 1 to 5 and / or the microwave absorbing material according to any one of claims 6 to 9.
Citation Information
Patent Citations
Light and flexible graphene based multi-element compound wave absorbing film and preparation method thereof
CN107840324A
Preparation method of magnetic nanoparticle / graphene / carbon fiber-based composite wave-absorbing material
CN110591642A
Electromagnetic wave absorbing material, wire rod and preparation method and application thereof
CN117924874A
Resin composition having electro-magnetic wave absorption function with high thermal radiation, and molded article manufacture by using the same
KR101579522B1